2021
DOI: 10.1177/03635465211028985
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Development of Preventive Strategies for Lateral Hinge Fracture During Opening Wedge High Tibial Osteotomy Based on Osteotomy Configurations

Abstract: Background: Lateral hinge fracture (LHF) is a major complication of opening wedge high tibial osteotomy (OWHTO) and may result in poor outcomes. Purpose/Hypothesis: The purpose of this study was to develop preventive strategies by identifying factors that affect LHFs. We hypothesized that (1) each LHF type would have different affecting factors and that (2) specific operative strategies that can contribute to the prevention of each LHF type can be developed. Study Design: Case-control study; Level of evidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…16,17,22 An LHF has been reported as an important factor associated with inaccurate correction and recurrence. 5,19,34 In the subgroup analysis of unfavorable radiological outcomes, DWBLR was the common significant factor associated with unfavorable radiological outcomes, except for a JLCA <0 and an LHF. For a JLCA <0 , which indicates a tendency for valgus overcorrection, only the JLCA parameters were significant.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…16,17,22 An LHF has been reported as an important factor associated with inaccurate correction and recurrence. 5,19,34 In the subgroup analysis of unfavorable radiological outcomes, DWBLR was the common significant factor associated with unfavorable radiological outcomes, except for a JLCA <0 and an LHF. For a JLCA <0 , which indicates a tendency for valgus overcorrection, only the JLCA parameters were significant.…”
Section: Discussionmentioning
confidence: 90%
“… 16 , 17 , 22 An LHF has been reported as an important factor associated with inaccurate correction and recurrence. 5 , 19 , 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al 13 reported that the coronal osteotomy slope was significantly larger in the LHF group than in the non-LHF group (20.3°± 5.1° vs 16.7°± 4.2°, respectively; P = .001). Choi et al 4 also reported that coronal osteotomy angle was one of the significant modifiable factors to prevent LHF in MOHTO. Lee et al 13 explained that if osteotomy is performed with an abrupt angle on the coronal plane in MOHTO, the thickness of the posterolateral bony bridge would be reduced and the risk of developing LHF would be increased.…”
Section: Discussionmentioning
confidence: 95%
“…The angle of the osteotomy line is increased because the osteotomy line is moved down to avoid the insertion point of the patellar tendon. An increase in the osteotomy line angle can also reduce the risk of type II fracture 35 . Although the distance between the tibial plateau and the crown of the fibula was 9.4 ± 2.8 mm, 36 because neither the bone knife nor the K‐wire penetrated the lateral cortex, the superior tibiofibular syndesmosis was not damaged by the surgical procedure.…”
Section: Discussionmentioning
confidence: 99%